2013
DOI: 10.1111/1556-4029.12124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Postmortem Bacterial Migration Using Culturing and Real‐Time Quantitative PCR

Abstract: Postmortem bacteriology can be a valuable tool for evaluating deaths due to bacterial infection or for researching the involvement of bacteria in various diseases. In this study, time-dependent postmortem bacterial migration into liver, mesenteric lymph node, pericardial fluid, portal, and peripheral vein was analyzed in 33 autopsy cases by bacterial culturing and real-time quantitative polymerase chain reaction (RT-qPCR). None suffered or died from bacterial infection. According to culturing, pericardial flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 29 publications
5
74
0
Order By: Relevance
“…The selection criteria for the autopsies have been described elsewhere [13]. None of the controls or cases was reported to has been used antibiotics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection criteria for the autopsies have been described elsewhere [13]. None of the controls or cases was reported to has been used antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…were designed and confirmed by using BLAST (http://www.ncbi.nlm.nih.gov/) and Ribosomal Database Project (http://rdp.cme.msu.edu/probematch/search.jsp). Specificity and cross reactivity of the designed primers and probes were tested using bacterial cultures from clinical samples [13]. PCR assays were performed with AbiPrism 7000 HT Sequence Detection System (Taqman, AppliedBiosystems, California, USA) with Taqman Environmental MasterMix.…”
Section: Resultsmentioning
confidence: 99%
“…Clostridium spp. are normal members of the human gut microflora, and have been reported as a prominent members of postmortem microbial communities, including both internal organs and external sites (Hyde et al, 2015; Javan et al, 2016; Tuomisto et al, 2013; Cobaugh, Schaeffer & DeBruyn, 2015; Metcalf et al, 2013; Can et al, 2014). Another Clostridiales, Anaerosphaera spp., have been previously isolated from animal waste reactors and identified as aminolytic anaerobes, fermenting amino acids into volatile fatty acids (Ueki et al, 2009), implicating them as members of the putrefactive consortia as well.…”
Section: Discussionmentioning
confidence: 99%
“…Another Clostridiales, Anaerosphaera spp., have been previously isolated from animal waste reactors and identified as aminolytic anaerobes, fermenting amino acids into volatile fatty acids (Ueki et al, 2009), implicating them as members of the putrefactive consortia as well. Mouse model studies examining translocation of bacteria postmortem have demonstrated the migration and proliferation of Clostridium and other anaerobic taxa in the internal organs with increasing postmortem intervals (Heimesaat et al, 2012; Burcham et al, 2016); an increase in Clostridium in human internal organs postmortem has also been reported (Javan et al, 2016; Tuomisto et al, 2013). Clostridia are known putrefactive organisms, so their observed increase in relative abundance may be due to an increase in vegetative growth, where they gained energy through the fermentation of cellular products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation